Mechanisms for funding youth businesses in South Africa: The role of DFIs - Mabasa, Nhlamulo Collins (Research of GSB, 2018)
South Africa has been experiencing an unprecedented increase in youth unemployment in the past 5 years and the level of entrepreneurial activities amongst young people is very low reported at 8.9% below international average of 11.9 % as at 2014. This situation still manifest itself even after the government of the Republic of South Africa (RSA) took a policy stance in tasking the National Development Agency (NYDA) to place youth entrepreneurship at the core of its programs to ensure that young people in their numbers participate in the mainstream economy. Previous research conducted in the country about the state or levels of youth entrepreneurship, attributed the shortcomings to funding gaps left by commercial banks, lack of business skills, lack of concerted efforts to have curriculum that is focused on entrepreneurship in universities but at the core of it all, funding is cited as the biggest challenge experienced by young people willing to start and run their own businesses. In the country with a sophisticated financial sector and DFIs highly liquid, yet we still have funding challenges and procedural bottlenecks experienced by sectors of society interested in establishing businesses. It is out of these challenges that this research seeks to investigate into the mechanisms used by South African DFIs (NYDA and Awethu projects) to fund youth enterprises in the country. This Research used a qualitative approach to analyse primary and secondary data collected from the NYDA, Awethu projects and IDC This research found that public DFIs have a wider reach compared to private DFIs because it is easy to set up offices in municipalities like the case of the NYDA and the IDC. Private DFIs will also struggle against public DFIs in servicing a wider range of youth enterprises because of government guarantees that could always be activated in times of financial stress. It also made a finding that Awethu projects emphasise the need for employment creation when qualifying enterprises from one funding band to the next compared to the NYDA. The three institutions have sound and functional credit committees that ensure that prejudice is eliminated from the appraisal processes. Lastly the NYDA spends majority of its budget on salaries compared to the mandate which it exists for. On average, about 39% of its budget goes to servicing internal human resource issues as compared to 8.31% budgeted to fund youth businesses.